Mozambique Diagnostic Review of Consumer Protection and Financial Literacy : Vol.1. Key Findings and Recommendations - World Bank Group (World Bank, Washington, DC, 2016)
The existence of a sound financial consumer protection framework is fundamental to increasing access to and usage of financial services, and the quality of those financial services, along with supporting further financial sector deepening. Financial consumer protection is a necessary precursor to building trust in the formal financial sector and thus in encouraging financial inclusion. Further, consumer protection helps ensure that expanded access benefits consumers and the economy as a whole. While increased access can result in significant economic and societal benefits, it can be neutral or even harmful if consumers: (i) cannot exercise their rights as consumers, (ii) cannot select the financial products that suit them best; and (iii) are not protected from mis-selling, fraud, and other market abuses. The main objective of a CPFL Review is to assess the legal, regulatory, and institutional frameworks for financial consumer protection in a country, with reference to the good practices. The following areas are addressed: (i) institutional arrangements, (ii) the legal and regulatory framework, (iii) transparency and disclosure, (iv) business practices, (v) complaints handling and dispute resolution mechanisms and (vi) financial literacy/capability. All parts of a financial sector can be considered, including banking, non-bank credit institutions, insurance, securities, private pensions, and credit reporting.